Morphology‐Controlled Organic Solar Cells Improved by a Nanohybrid System of Single Wall Carbon Nanotubes Sensitized by PbS Core/Perovskite Epitaxial Ligand Shell Quantum Dots. Issue 8 (27th June 2017) - Soltani, Rezvan; Katbab, Ali Asghar; Sytnyk, Mykhailo; Yousefi Amin, Amir Abbas; Killilea, Niall; Berlinghof, Marvin; Ahmadloo, Farzaneh; Osvet, Andres; Unruh, Tobias; Heiss, Wolfgang; Ameri, Tayebeh
Abstract : In the present work, a new solution processed nanohybrid system comprising of single‐wall carbon nanotubes (SWCNTs) loaded by PbS quantum dots (QD) capped with an epitaxial ligand shell of methylammonium lead iodide perovskite clusters (MA4 PbI6 ) is designed and fabricated. Attachment of PbS/PbI6 QDs on the surface of SWCNT is followed and evidenced by performing Fourier Transform Infrared Spectroscopy, X‐ray photoelectron spectroscopy, and Field Emission Scanning Electron Microscopy. The steady state and dynamic photoluminescence results reveal efficient charge transfer from photo‐excited PbS/PbI6 to SWCNTs. Very low amount (0.3 wt.%) of the as‐synthesized PbS/PbI6 ‐SWCNT is further incorporated into a polymeric solar cell containing P3HT and PC61 BM and exhibits a power conversion efficiency improvement of around 15% compared to the P3HT:PC61 BM bulk heterojunction reference solar cell. Significantly, loading perovskite capped PbS QDs on the surface of SWCNT works more efficient rather than incorporating PbS/PbI6 or SWCNT separately onto the composition of the photoactive layer. While PbS/PbI6 broaden the absorption window of photoactive layer and enhance the photon harvesting, their loading on the SWCNT has a significant influence on the faster exciton splitting by efficient electron transfer as well as keeping the desired crystallinity and nanoscale morphology of host matrix upon addition of QDs. Abstract : The power conversion efficiency of P3HT:PC61 BM solar cells is improved by incorporation of SWCNT loaded by PbS quantum dots capped with an epitaxial ligand shell of methylammonium lead iodide perovskite clusters, owing to the enhanced J SC resulted from larger light harvesting, facilitated exciton dissociation, and higher charge transport.